Citizen utilities: The emerging power paradigm - Green, Jemma; Newman, Peter (Elsevier Science, 2017)
The emergence of citizen-based power systems in an integrated grid has been anticipated for decades. We can reveal how this is emerging in practice due to the significant uptake of solar photovoltaics (solar PV) and now battery storage in Perth, Australia. The high cost of electricity, high radiant energy levels and easy access to cheap Chinese technology, has led to dramatic buying during Perth's recent boomtown years. The traditional uni-directional power system is rapidly disrupting and this paper assesses where this may lead and what it means for the grid. Results of detailed monitoring in a solar powered house along with the impact of a battery storage system show the impact on the traditional grid is substantial but it will still be needed and must therefore adapt to the new distributed, bi-directional energy system. Surveys and price trajectories reveal how the trends to solar power storage will continue and how a citizen utility paradigm will emerge as the future grid building block using new blockchain support systems. Responses from utilities are then see to be fight, flight or innovate.